Variation in landmarks for the rectum: an MRI study. (26th September 2018) - D'Souza, N.; Balyasnikova, S.; Tudyka, V.; Lord, A.; Shaw, A.; Abulafi, M.; Tekkis, P.; Brown, G.
Abstract: Aim: This study aimed to assess the reliability of measurements and bony landmarks for the rectosigmoid junction on MRI. Method: The staging MRI scans for 100 patients were reviewed. The junction of the mesorectum and mesocolon was used to identify the rectum and sigmoid. The performance of current metric measurements or bony landmarks was then compared against the actual anatomical bowel segment. Results: The mean distance of the sigmoid take‐off from the anal verge was 12.6 cm (SD 1.8 cm, range 9.4–19.0 cm). At a cutoff of 12 cm, the anatomical bowel segment was found to be sigmoid colon rather than rectum in 35% of patients. At 15 and 16 cm the bowel segment was sigmoid in 84% and 96% of patients, respectively. At the sacral promontory and the third sacral segment, the bowel segment was sigmoid in 28% and 100% of patients, respectively. Conclusion: Current definitions of the rectum that rely on arbitrary measurements or bony landmarks will not locate the correct point of transition between the rectum and sigmoid in the majority of patients. The sigmoid take‐off offers an alternative, anatomically bespoke, landmark.